Fragilidade em idosos longevos: associação com doenças crônicas e consumo de medicamentos - Silva, Francisca Juliana de Assunção (2018)
The objective of this study was to verify the association of SF with the presence of chronic non-transmissible diseases and the use of polypharmacy (≥ 5 drugs) comes aged long-lived. Method: This is a cross-sectional, descriptive study with a quantitative approach. The population studied was elderly people (≥ 80 years old), participants in the project Physical, cognitive and psychosocial aging patterns in elderly people living in different contexts, in Brasília, Federal District. The data were collected in two sessions, the first one in the geriatrics outpatient clinics of the Catholic University of Brasília (UCB), where the questionnaires of identification and sociodemographic and verified in the medical records were diagnosed for chronic noncommunicable diseases diagnosed by a physician in the last year, as well as the use, in this same period, of polypharmacy. In the second session, in the laboratory LAFIT of the UCB, carried out evaluation of five measures of SF. Data analysis was done with anova two-way and chi-square test. Conclusion: Although a low prevalence of frailty was detected in the long-lived population studied, the prevention of this syndrome as it was found in the study population was found to be predominantly female, marital status, white race and low schooling. advances the age, especially in the pre-frail elderly, must be performed by health professionals in a multi and interdisciplinary way, seeking to provide an active aging and a better quality of life for this population.